Transcriptome Insights into Carbohydrate Metabolism and Frying Quality Traits in Waxy and Mealy Potatoes - Jeong-Jin Choi; Do-Hee Kwon; Jang-Gyu Choi; Gyu-Bin Lee; Jae-Youn Yi; Hui-Tae Lee; Hong-Sik Won; Young-Eun Park; Yong-Ik Jin; Dong-Chil Chang; Kwang-Soo Cho (Agronomy, 2025)
The fried potato market is a high-value industry, exceeding USD 55 billion and still growing. However, the genetic mechanisms underlying key frying traits remain poorly understood. In this study, we conducted a transcriptome analysis on two types of potatoes with distinct end-use purposes to identify the gene expression profiles related to desirable frying qualities, focusing on texture and appearance after frying. Key genes encoding starch synthase 1 and 3, sucrose synthase 4, invertases, and pectin methyl-esterase inhibitors were found to be differentially regulated in waxy and mealy potatoes based on their frying characteristics. Notably, mealy potatoes exhibited a higher expression of starch synthesis-related genes and a lower expression of invertase genes. These expression patterns may enhance glucose-to-starch conversion, thereby reducing glucose levels and minimizing sugar-induced browning, which results in a lighter fried appearance. Additionally, we identified two transcription factors, StbZIP2 and StbZIP35, that are potentially co-expressed with two starch synthases. These transcription factors are responsive to abscisic acid, a key hormonal regulator involved in tuber development. This study provides transcriptomic insights for processing quality improvement and identifies key candidate genes for marker-assisted breeding. Further studies across more diverse samples with integrative multi-omics approaches will strengthen the application of these insights in breeding programs.